Household solid fuel use and stroke incidence: Evidence from a national cohort study - Zhang, Hehua; Xia, Yang; Su, Han; Chang, Qing; Zhao, Yuhong (Frontiers in Public Health, 2022)
Stroke is one of the leading causes of global mortality and disability. No specific study has focused on the association between household solid fuel use for different purposes and incident stroke. Therefore, we explored the associations between household solid fuel use purposes and switches and incident stroke based on a national prospective cohort study. There were 12,485 participants included in this study after exclusions. The incidence density of stroke was 8.29 for every 1000 person-years. Household solid fuel use simultaneously for heating and cooking had the largest hazard effect on stroke occurrence (hazard ratio [HR], 1.35; 95% confidence interval [CI], 1.07, 1.70) with a significant linear trend (P < 0.01). Solid fuel use for cooking was significantly associated with increased risk of stroke occurrence (HR, 1.27; 95% CI, 1.06, 1.51). Persistent clean fuel use for both heating and cooking associated with a lower risk of stroke occurrence (HR, 0.79; 95% CI: 0.64, 0.99), and switching from solid fuel to clean-fuel use for cooking associated with a lower risk of stroke occurrence (HR, 0.89; 95% CI, 0.73, 1.09) compared with persistent solid fuel use. Effective measures to improve the household cooking environment may be necessary to prevent incident stroke.